Pengembangan Media Puzzle Book pada Materi Pengukuran Sudut Siswa Kelas III UPT SD Negeri 47 Gresik - Tanti Yusviva Kusuma Wardani; Arissona Dia Indah Sari; Iqnatia Alfiansyah (Edukasi Elita : Jurnal Inovasi Pendidikan, 2026)
This study aims to develop a Puzzle Book learning media for the topic of angle measurement and to examine its validity, practicality, and effectiveness for third-grade elementary school students. The research employed a Research and Development (R&D) approach using the ADDIE model and involved 26 third-grade students as participants. Data were collected through expert validation sheets, student response questionnaires, and learning achievement tests, which were analyzed using descriptive quantitative and qualitative methods. The results showed that the Puzzle Book obtained a validity score of 98.0% from media experts and 100% from material experts, both categorized as highly valid. Student responses reached 100%, indicating that the media is highly practical and engaging. Furthermore, the analysis of learning outcomes revealed a gain score of 0.9187 in the high category, demonstrating that the Puzzle Book effectively improves students’ problem-solving abilities in angle measurement. Overall, the Puzzle Book learning media is highly feasible, practical, and effective for classroom implementation, as its interactive design and alignment with third-grade learning characteristics help students understand angle concepts more concretely, enjoyably, and meaningfully.